Evaluation of Cross Protective Efficacy of Commercial Vaccines against Mannheimia haemolytica in Mice: Waffa A.Ahmed, Asmaa H. Abdullah, Ansam K. Mohammed and Roua J. Mohammed - Ahmed, Waffa A. (The Iraqi Journal of Veterinary Medicine, 2019)
Mannheimia haemolytica together with Pasteurella multocida represents as a major bacterial causative agent of cattle, sheep and goats respiratory diseases and its one of the most important causes for economic losses to these animals .Commercially available vaccines were used to prevent infections caused by P. multocida and M. haemolytica. Thus, the aim of the present study was to evaluate the cross protection efficacy of two vaccines to protect mice against M.haemolytica, studying humeral immunity, using Enzyme-Linked Immunosorbent Assay. Forty five mice were divided into three equal groups, group one and two were inoculated subcutaneously 4μl® and 1μl of Al-kindy vaccines respectively, while the third group was with 0.5 ml sub cutaneous PBS. LD50for M.haemolytica was estimated as 2× 106 cfu and challenge test was conducted by dropping 0.05 ml 2× 106 cfu intranasally after three weeks of immunization for the three groups. The results of Enzyme-Linked Immunosorbent Assay, showed significant increase of antibody titters at (P<0.01) in (group 1 and 2) after first and second weeks post immunization, in comparison with control group. Also, the re-isolation of M.haemolytica from lungs tissue of all groups after challenged were positive with significant difference between control and immunized group, control group was 4× 108 cfu ∕ml which was higher than immunized group one and group two,which were 2.5×104 cfu∕ml and 3,5×105 cfu∕ml respectively after 24 hour of vaccine. In conclusion, the two commercial vaccines showed good cross protection efficacy against M. haemolytica, but JOVAPAST® vaccine showed higher efficacy than Alkindy vaccine, as that it contain two heterologous killed strains and providing the basis for production a vaccine from the two pathogen of local strains.